Neuroendocrine tumor of appendix located Spiegel hernia – case report and review of the literature - Karahan, Furkan; Atay, Arif; Ekinci, Neşe; Gür, Emine Özlem; Dilek, Osman Nuri (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Appendix, located within the Spiegel hernia is a rare condition. Few cases have been reported to date. Although it is generally asymptomatic, patients can apply with strangulation findings. Along with the physical examination findings, imaging methods play an important role in diagnosis and definitive diagnosis is made intraoperatively. Per-operative surgical method is determined according to the condition of the structures in the hernia sac. If an appendix is detected in the hernia sac, appendectomy is often preferred regardless of symptoms. Postoperative pathology is mostly benign but malign appendix pathologies should be kept in mind. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Here, we aimed to present our case undergoing emergency surgery due to incarcerated hernia as it is the first case of appendix neuroendocrine tumor in the Spiegel hernia sac according to our literature review. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 77-year-old female patient who was admitted to the hospital with complaints of nausea and vomiting was evaluated as an emergency. In the clinical evaluation of the patient, we detected ileus due to hernia. We operated on the patient and found the appendix and cecum in the spiegel hernia. We did appendectomy and hernia repair. Histopathological examination of the appendix revealed a well-differentiated neuroendocrine tumor. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Detection of the appendix in a Spiegel hernia is a rare condition. This is the first case of appendiceal malignancy in a Spiegelian hernia.